EVALUASI BIJI TANAMAN GAMAL PROVENAN RETALHULEU PADA LAHAN KERING DI BUKIT BADUNG BALI - A.W. Puger; I.W. Suberata; I.G.E. Putra; I.M. Suarn; I.M. Nitis (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
Gliricidia (Gliricidia sepium) provenance Retalhuleu seed garden has been established in 1992 in dry land farming at Bukit Pecatu Village, Bukit Badung Peninsula, South Bali, at 100m sea level, on red-brown mediteran calcareous-base soil, with 1552 mm rainfall, distributed during 4 months wet season and 8 months dry season. The Completely Randomized Block Design Arrangement consisted of 60 famili(F) as treatments, 6 blocks as replications and 10 plants per treatment were used in this experiment. The first harvest was carried out in November 1995 and the subsequent harvest was carried out in October-November each year. Results of 11nd harvests (16 year plant age) on seed production and quality showed that famili F12, F17 and F51 (ranking order) could be registered (priority rights) as planting.